Relationship of Bradykinin B-2 Receptor Gene C-58T Variation with Total-Cholesterol and Glucose in Essential Hypertension - SÜSLEYİCİ, BELGİN; ZENGİN, SENİYYE ÜLGEN (BEZMIALEM VAKIF UNIV, 2016)
Objective: Hypertension, which affects 25% of the world's population, is a complex disease, with 30% genes affecting its pathogenesis. In this study, we aimed to examine the frequency of the bradykinin B-2 receptor gene C-58T genotypes in patients with essential hypertension and non-hypertensive controls. In addition, we evaluated the effects of C-58T genotypes on demographic characteristics, phenotypes related to obesity, and hypertension. Methods: Genotyping was performed in 63 hypertensive patients and 56 non-hypertensive subjects by PCR-RFLP. Results: The frequency of bradykinin B-2 receptor gene C-58T genotypes in hypertensive patients and control subjects was 25.4% and 28.6% for homozygous wild-type (T/T), 49.2% and 58.9% for heterozygous (T/C), and 25.4% and 12.5% for homozygous polymorphic (C/C) genotypes, respectively. Genotype frequencies did not differ significantly among study groups. The C allele was found to have an increasing effect on blood glucose levels (p=0.05) and decreasing effect on total cholesterol levels (p=0.008) in hypertensive patients, whereas it was found to have an increasing effect on waist circumference (p=0.041) in control subjects. Hypertensive patients with C allele were found to use sulfonylurea drugs (p=0.021) at a higher frequency than those with T allele. Further, hypertensive patients with T allele were found to use diuretic drugs (p=0.007) at a higher frequency than those with C allele. Conclusions: The C-58T polymorphism is found to have a positive association with total cholesterol levels, blood glucose levels, and waist circumference but no association with systolic/diastolic blood pressure.
Keywords: Bradykinin; hypertension; cholesterol; waist circumference; blood glucose; EXERCISE-INDUCED INCREASE; I-CONVERTING-ENZYME; SKELETAL-MUSCLE; B2 RECEPTOR; BLOOD-PRESSURE; PHARMACOLOGICAL CHARACTERIZATION; SEQUENCE-ANALYSIS; ANGIOTENSIN; EXPRESSION; TRANSPORT